Evaluation of Sofosbuvir (β-D-2′-deoxy-2′-α-fluoro-2′-β-C-methyluridine) as an inhibitor of Dengue virus replication # - Xu, Hong-Tao; Palanisamy, Navaneethan (Scientific reports, 2017)
We evaluated Sofosbuvir (SOF), the anti-hepatitis C virus prodrug of β-d-2′-deoxy-2′-α-fluoro-2′-β-C-methyluridine-5′-monophosphate, for potential inhibitory activity against DENV replication. Both cell-based and biochemical assays, based on use of purified DENV full-length NS5 enzyme, were studied. Cytopathic effect protection and virus yield reduction assays confirmed that SOF possessed anti-DENV activity in cell culture with a 50% effective concentration (EC50) of 4.9 µM and 1.4 µM respectively. Real-time RT-PCR verified that SOF inhibits generation of viral RNA with an EC50 of 9.9 µM. Purified DENV NS5 incorporated the active triphosphate form (SOF-TP) into nascent RNA, causing chain-termination. Relative to the natural UTP, the incorporation efficiency of SOF-TP was low (discrimination value = 327.5). In a primer extension assay, SOF-TP was active against DENV NS5 wild-type polymerase activity with an IC50 of 14.7 ± 2.5 µM. The S600T substitution in the B Motif of DENV polymerase conferred 4.3-fold resistance to SOF-TP; this was due to decreased incorporation efficiency rather than enhanced excision of the incorporated SOF nucleotide. SOF has antiviral activity against DENV replication. The high discrimination value in favor of UTP in enzyme assays may not necessarily preclude antiviral activity in cells. SOF may be worthy of evaluation against severe DENV infections in humans.